Anti-lymphocyte, anti-monocyte, and anti-endothelial cell antibodies in chronic haemodialysis patients - DİRESKENELİ, RAFİ HANER (My University, 1992)
Patients receiving chronic haemodialysis treatment are known to have a high prevalence of anti-panel antibodies (anti-lymphocyte, antimonocyte, and anti-endothelial cell) originating from a number of different possible sensitizing events such as blood transfusions, multiparity, or renal transplantation. © 1992 European Dialysis and Transplant Association-European Renal Association.
Keywords: Chronic haemodialysis; Panel-reactive antibodies; Sensitization; Transfusion